(untitled) (Research, Society and Development, 2020)
This paper aims to present the experiences of an extension project of the Gastronomy Course at the Universidade Federal do Ceará (UFC). The project was carried out in five full-time high schools in Fortaleza in the years 2017 to 2020, seeking to create a learning environment for food and nutrition education to develop quality food and the construction of healthy and sustainable eating habits. UFC students carried the project, coordinated by professors from the Gastronomy Course, who worked in planning, developing, and evaluating activities, research instruments, and generated products. High school students were instructed on healthy eating practices, analyzing these students’ nutritional status and eating habits, and implementing a school vegetable garden for growing vegetables. The extension actions of the UFC Gastronomy Course have contributed to the construction of knowledge and attitudes related to food and sustainability in school environments, actively contributing to the food and nutritional security of the young people assisted. It is an initiative that needs to be expanded considering that despite the relevance of the theme, Food and Nutrition Security activities do not occur effectively in most schools integrating food production practices with social, environmental, and nutritional care, as provided be experienced in that extension project.